Novel hybrids of natural β-elemene bearing isopropanolamine moieties: synthesis, enhanced anticancer profile, and improved aqueous solubility - Chen, Jichao; Wang, Tianyu; Xu, Shengtao; Aijun, Lin; Yao, Hequan; Xie, Weijia; Zhu, Zheying; Xu, Jinyi (Elsevier, 2017)
A series of novel β-elemene isopropanolamine derivatives were synthesized and evaluated for their antitumor activity. The results indicated that all of the compounds showed stronger antiproliferative activities than β-elemene as well as improved aqueous solubility. In particular dimer 6q showed the strongest cytotoxicity against four tumor cell lines (SGC-7901, HeLa, U87 and A549) with IC50 values ranging from 4.37 to 10.20 μM. Moreover, combination of 6q with cisplatin exhibited a synergistic effect on these cell lines with IC50 values ranging from 1.21 to 2.94 μM, and reversed the resistance of A549/DPP cells with an IC50 value of 2.52 μM. The mechanism study revealed that 6q caused cell cycle arrest at the G2 phase and induced apoptosis of SGC-7901 cells through a mitochondrial-dependent apoptotic pathway. Further in vivo study in H22 liver cancer xenograft mouse model validated the antitumor activity of 6q with a tumor inhibitory ratio (TIR) of 60.3%, which was higher than that of β-elemene (TIR, 49.1%) at a dose of 60 mg/kg. Altogether, the potent antitumor activity of 6qin vitro and in vivo warranted further preclinical investigation for potential anticancer chemotherapy.